The PhoPQ Two-Component System Is the Major Regulator of Cell Surface Properties, Stress Responses and Plant-Derived Substrate Utilisation During Development of Pectobacterium versatile-Host Plant Pathosystems - Kravchenko, Uljana; Gogoleva, Natalia; Kalubaka, Nastassia; Kruk, Alla; Diubo, Yuliya; Gogolev, Yuri; Nikolaichik, Yevgeny (Frontiers in Microbiology, 2021)
Pectobacterium versatile (formerly P. carotovorum) is a recently defined species of soft rot enterobacteria capable of infecting many plant hosts and damaging different tissues. Complex transcriptional regulation of virulence properties can be expected for such a versatile pathogen. However, the relevant information is available only for related species and is rather limited. The PhoPQ two-component system, originally described in pectobacteria as PehRS, was previously shown to regulate a single gene, pehA. Using an insertional phoP mutant of Pectobacterium versatile (earlier – P. carotovorum), we demonstrate that PhoP regulates at least 115 genes with a majority of them specific for pectobacteria. The functions performed by PhoP-controlled genes include degradation, transport and metabolism of plant-derived carbon sources (polygalacturonate, arabinose-containing polysaccharides and citrate), modification of bacterial cell envelope and stress resistance. We also demonstrated PhoP involvement in establishing the order of plant cell wall decomposition and utilisation of the corresponding breakdown products. Based on experimental data and in silico analysis, we defined a PhoP binding site motif and provided proof for its universality in enteric bacteria. Scanning P. versatile genome for the locations of this motif suggested a much larger PhoP regulon enriched with the genes important for a plant pathogen, which makes PhoP a global virulence regulator. Potential PhoP targets include many regulatory genes and PhoP control over one of them, expI, was confirmed experimentally, highlighting the link between the PhoPQ two-component and quorum sensing systems. High concentrations of calcium and magnesium ions were found to abolish the PhoPQ-dependent transcription activation but did not relieve repression. Reduced PhoP expression and minimisation of PhoP dependence of regulon members’ expression in P. versatile cells isolated from potato tuber tissues suggest that PhoPQ system is a key switch of expression levels of multiple virulence-related genes fine-tuned to control the development of P. versatile-host plant pathosystem.